Aaron B. Tompkins correspondence - Tompkins, Aaron B.
Letters written by Tompkins to his mother and sister while serving in the 1st New Jersey Cavalry Regiment in Virginia and Maryland during the Civil War. Mentions George Armstrong Custer and John Singleton Mosby and skirmishes around Warrenton, Petersburg, and Richmond, Va.
Typewritten transcripts of the letters are also available.
Soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Custer, George A. -- 1839-1876.; Mosby, John Singleton, -- 1833-1916.; United States. -- Army -- History -- Civil War, 1861-1865.; United States. -- Army. -- New Jersey Cavalry Regiment, 1st (1861-1865); Maryland -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Civil War, 1861-1865.; Richmond (Va.) -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Warrenton (Va.) -- History; Soldiers